RESILIENCE OF CUSTOMARY LAW IN FACING THE ECOLOGICAL CRISIS IN PAYA NIE - Fitri Maghfirah; Marlia Sastro; Sela Azkia; Muhammad Yusra; Nanda Setia Saputra (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This study employs a qualitative socio-legal approach to examine the role of customary law in addressing climate change and ecological challenges in the Paya Nie wetland ecosystem. Customary law is understood not only as written norms but also as living practices embedded in community life. Thus, the ecological crisis in Paya Nie marked by recurrent drought, flooding, and ecosystem degradation cannot be analyzed solely through normative legal perspectives but requires a broader socio-ecological framework. Research data were obtained from two main sources. Secondary data came from academic journals, legal documents, government reports, and research publications, providing the conceptual foundation to situate customary law within environmental governance. Primary data were collected through participatory observation and in-depth interviews with customary leaders, local stakeholders, and surrounding communities to capture social dynamics, communal solidarity, and unwritten customary mechanisms that remain influential in daily practice. Data were analyzed using a descriptive-analytical method. The analysis first mapped ecological problems in Paya Nie, then linked them to customary and formal legal instruments, including qonun gampong. Finally, the findings were interpreted through the lens of socio-ecological resilience theory to reveal how communities adapt, transform, and innovate in response to climate change. The study shows that customary law in Paya Nie functions not only as a set of traditional rules but also as an adaptive mechanism that strengthens community resilience. It plays a critical role in regulating land use, fostering solidarity, and sustaining ecological balance. These findings contribute to the broader discourse on how living customary law can serve as a local strategy for ecological resilience in the face of global environmental change.